2014
DOI: 10.1097/cej.0000000000000030
|View full text |Cite
|
Sign up to set email alerts
|

Light exposure at night, sleep duration, melatonin, and breast cancer

Abstract: Evidence from observational studies on light at night (LAN) exposure, sleep duration, endogenous melatonin levels, and risk for breast cancer in women is conflicting. This led us to conduct a dose-response analysis of published observational data. Pertinent studies were identified by searching Medline, Web of Science, and EMBASE through April 2013. The dose-response relationship between sleep duration, urinary 6-sulphatoxymelatonin levels, and breast cancer was assessed using the restricted cubic spline model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 38 publications
3
54
1
Order By: Relevance
“…Evidence from such studies led the International Agency for Research on Cancer (IARC) to declare shiftwork with circadian disruption to be "probably carcinogenic to humans (Group 2A)" (5). However, pooled breast cancer risks of female night shift workers based on meta-analyses of available studies vary and range from a 5-51% increase in risk (6)(7)(8)(9)(10)(11)(12)(13)(14). While an association between breast cancer and working nights may be due to the effect of LAN on melatonin levels, other aspects of working at night, such as reduced sleep may also be involved in tumor development or growth.…”
mentioning
confidence: 99%
“…Evidence from such studies led the International Agency for Research on Cancer (IARC) to declare shiftwork with circadian disruption to be "probably carcinogenic to humans (Group 2A)" (5). However, pooled breast cancer risks of female night shift workers based on meta-analyses of available studies vary and range from a 5-51% increase in risk (6)(7)(8)(9)(10)(11)(12)(13)(14). While an association between breast cancer and working nights may be due to the effect of LAN on melatonin levels, other aspects of working at night, such as reduced sleep may also be involved in tumor development or growth.…”
mentioning
confidence: 99%
“…Two more recent meta-analyses focusing exclusively on breast cancer found no evidence that sleep duration was associated with increased incidence (Yang et al, 2014; Qin et al, 2014). Both reviewed the same six studies, all that had been published on sleep duration and breast cancer through 2013.…”
Section: Sleep Disruption and Breast Cancer Oncogenesis: Expanding Thmentioning
confidence: 98%
“…Eight of the meta-analyses reported an overall increased incidence of breast cancer (ranging from 5 to 48%) in women exposed to some form of circadian disruption, including lifetime exposure to night shift work and LAN (He et al, 2015a; Megdal et al, 2005; Jia et al, 2013; Kamdar et al, 2013; Wang et al, 2013; Ijaz et al, 2013; Yang et al, 2014; Lin et al, 2015). Furthermore, six of the metaanalyses conducted sub-analyses on years and nights of exposure, with converging evidence from five of the six studies suggesting that circadian disruption is associated with increased risk in a dose-dependent manner (Wang et al, 2013; Ijaz et al, 2013; Yang et al, 2014; Lin et al, 2015; He et al, 2015b). Kamdar and colleagues (Kamdar et al, 2013) did not find that participants working 8 or more years of NSW were at greater risk for developing breast cancer compared to non-shift workers, and Jia and colleagues (Jia et al, 2013) found that women working 15 or more years of NSW were not at increased risk above and beyond women who reported ever working night shift.…”
Section: The Circadian Disruption and Breast Cancer Pathogenesis Modelmentioning
confidence: 99%
“…Theoretically, exposure to bright light during the shift might reduce sleepiness by inhibiting the secretion of the sleep-promoting circadian hormone melatonin, but problems with trial designs have led to inconclusive results 82122. Furthermore, diminished night time levels of melatonin, which also functions as an antioxidant, have been suggested as a cause for increased cancer rates in shift workers 23. Given the limited evidence that such interventions can correct the deficit in night time psychomotor performance, we advocate mitigating risk to patients by building in extra checks during critical tasks, especially towards the physiological nadir in the early hours of the morning 2425…”
Section: What Evidence Is Available Regarding Strategies For Workers mentioning
confidence: 99%